The safety of drinking bottled water based on law of negligence : Malaysian perspectives. - Razman, Muhammad Rizal; Azlan, Azrina (Medwell Journals, 2008)
The law of negligence plays an inmportant role in protecting individual from polluted and contaminated drinking water. The use of the law of negligence in the area of an individual's protections is largely in reply to the neccesity of each individual tp protect his right and interest in consuming drinking water. Therefore, this wil examine the use of the law of negligence in relation to the individual protection on the drinking water safety from Malaysian legal perspectives, identify cases and actions which deals with the individual protection on polluted and contaminated drinking water from the Malaysian legal perspectives and lastly, discuss the law of negligence as a means to protect individual from the polluted and contaminated drinking water in Malaysia.